Immunity against measles, mumps, rubella, and varicella among homeless individuals in Germany — A nationwide multi-center cross-sectional study - Graf, Wiebke; Bertram, Franziska; Dost, Katharina; Brennecke, Anna; Kowalski, Veronika; van Rüth, Victoria; Nörz, Dominik Sebastian; Wulff, Birgit; Ondruschka, Benjamin; Püschel, Klaus; Pfefferle, Susanne; Lütgehetmann, Marc; et al. (Frontiers in Public Health, 2024)
Introduction Homeless individuals suffer a high burden of vaccine-preventable infectious diseases. Moreover, they are particularly susceptible to adverse infection outcomes with limited access to the health care system. Data on the seroprevalence of measles, mumps, rubella, and varicella within this cohort are missing. Methods The seroprevalence of measles, mumps, rubella, and varicella was determined within the homeless population in Germany. Predictors of lacking immune protection were determined using multivariable logistic regression analysis. Results Homeless individuals in Germany (n = 611) showed a seroprevalence of 88.5% (95% CI: 85.8–91.0) for measles, 83.8% (95% CI: 80.6–86.6) for mumps, 86.1% (95% CI: 83.1–88.7) for rubella, and 95.7% (95% CI 93.8–97.2) for varicella. Measles seroprevalences declined from individuals born in 1965 to individuals born in 1993, with seroprevalences not compatible with a 95% threshold in individuals born after 1980. For mumps, seroprevalences declined from individuals born in 1950 to individuals born in 1984. Here, seroprevalences were not compatible with a 92% threshold for individuals born after 1975. Seronegativity for measles, mumps and rubella was associated with age but not with gender or country of origin. Discussion Herd immunity for measles and mumps is not achieved in this homeless cohort, while there was sufficient immune protection for rubella and varicella. Declining immune protection rates in younger individuals warrant immunization campaigns also targeting marginalized groups such as homeless individuals. Given that herd immunity thresholds are not reached for individuals born after 1980 for measles, and after 1975 for mumps, vaccination campaigns should prioritize individuals within these age groups.